Artificial intelligence and mental health - dos Santos, Paula Isabel Gonçalves; Rosinhas, Ana Catarina (Seven Editora, 2023)
This article presents an overview of AI in mental health care, notably discusses its potential benefits, limitations, ethical implications, and future considerations for the use of AI in mental health care. Carrying out a reflection on the importance that this can have in the quality of life and mental health, emphasizing the uniqueness of the human being, its magical, unpredictability and creative capacity, concluding that AI should never replace the relationship, but on the contrary, be the support. In short, there is the need not to close the doors to reflection. DOI:https://doi.org/10.56238/innovhealthknow-020